Early and Midterm Results of No-Touch Aorta Multivessel Small Thoracotomy Coronary Artery Bypass Grafting: A Propensity Score–Matched Study. Issue 4 (July 2015) - Ziankou, Aliaksandr; Ostrovsky, Yuri
Abstract : Objective: To carry out the comparative analysis of early and midterm results of no-touch aorta multivessel small thoracotomy coronary artery bypass grafting (MVST CABG), conventional off-pump (OPCABG) and on-pump CABG (ONCABG). Methods: From 2007 to 2014, 537 consecutive patients underwent CABG by the same surgeon. Propensity score computer matching was performed, and a total of 453 patients were successfully matched in 3 groups of 151 patients. Results: Significant differences were found in the intraoperative blood loss: 220 (180; 300) mL in MVST CABG versus 400 (300; 550) mL in OPCABG vs 350 (250; 435) mL in ONCABG group; first 24-hour postoperative blood loss: 170 (100; 280), 320 (200; 470), and 380 (200; 500) mL, respectively; operation time: 352.4 ± 74.4, 289.3 ± 55.0, and 280.4 ± 56.4 minutes, respectively; median time to return to full physical activity: 14, 56, and 56 days, respectively ( P < 0.05); rate of deep wound infection: 0.0%, 2.0%, and 2.0%, respectively; and postoperative length of stay (surgical department): 4.5, 7.0, and 7.5 days, respectively ( P < 0.1). No significant differences were observed in rates of severe in-hospital events ( P > 0.05), cumulative midterm survival, and freedom from major adverse cardiac and cerebrovascular events ( P > 0.05). Conclusions: The MVST CABG seems as safe as OPCABG and ONCABG and is associated with less wound infections, perioperative blood loss, shorter hospital length of stay and time to return to full physical activity. Multivessel small thoracotomy CABG can be applied to most patients with coronary heart disease saving the effectiveness during midterm follow-up. The MVST CABG can be introduced avoiding a prolonged learning curve.